A study on effect of credit card on customer satisfaction in chennai - ROBERT. P, WILLIAM; A, MAHESHWAR. (The journal of contemporary issues in business and government, 2020)
Banking sector growth is infinite due to various innovation services.The main reason for this study is to determine the Effect of Credit Cards on Customer Satisfaction in Chennai and to know about the factors which influence customer satisfaction. The data is collected on probability basis from 107 respondents by using Convenience sampling and is analyzed with the SPSS tool. The collected data were classified, tabulated and analyzed with statistical tools Frequency analysis, Mean analysis, Independent t test one way anova and Regression analysis. The results showed that the majority of the respondents were male and aged 18- 25 years who use credit cards. The result shows that the customers are agreeing towards credit cards and the factors of credit card influencing the customer satisfaction.